2011
DOI: 10.1021/ac102897h
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping of Arrayed Microfluidic Systems in Polystyrene for Cell-Based Assays

Abstract: Microfluidic cell-based systems have enabled the study of cellular phenomena with improved spatiotemporal control of the microenvironment and at increased throughput. While PDMS has emerged as the most popular material in microfluidics research, it has specific limitations that prevent microfluidic platforms from achieving their full potential. We present here a complete process, ranging from mold design to embossing and bonding, that describes the fabrication of polystyrene (PS) microfluidic devices with simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(157 citation statements)
references
References 57 publications
1
156
0
Order By: Relevance
“…However, the plasma treatment can significantly affect the thermopress bonding strength because of surface reaction due to the plasma [22]. Moreover, it is noticed during our experiments that washing the PS films using DI water after oxygen plasma treatment can affect the bonding strength.…”
Section: Ps Thermopress Bonding Strength Testmentioning
confidence: 79%
“…However, the plasma treatment can significantly affect the thermopress bonding strength because of surface reaction due to the plasma [22]. Moreover, it is noticed during our experiments that washing the PS films using DI water after oxygen plasma treatment can affect the bonding strength.…”
Section: Ps Thermopress Bonding Strength Testmentioning
confidence: 79%
“…Although devices in the current work were fabricated in PDMS and glass, our platform can also be fabricated in polystyrene, 41 a thermoplastic widely used in common cell culture labware and useful for studies involving small hydrophobic molecules (eg, estrogen, fluoxetine) that are known to absorb into bulk PDMS. [42][43][44] We validated the platform in the context of MM and showed that other suspension cell types (CLL) can also be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Polymers such as polydimethylsiloxane (PDMS) [5,6], polymethylmethacrylate (PMMA) [7,8], polystyrene (PS) [9], polycarbonate (PC) [10,11] and cyclin olefin copolymer (COC) [12] are fabricated using methods such as soft lithography, hot embossing, micromolding and laser micromachining techniques. Despite their widespread use, functional integration of components including electronics, heaters, electrodes, optoelectronics, and sensing elements remains a challenge [13].…”
Section: Page 2 Ofmentioning
confidence: 99%